Thermoplastic elastomer molded body, composite molded body, and manufacturing method

By using a molded body of a specific composition in the thermoplastic elastomer molded body, the problem of insufficient bonding with glass peeling and member in the prior art is solved, and efficient sound suppression and excellent bonding properties are achieved.

CN119570143APending Publication Date: 2025-03-07SUMITOMO CHEM CO LTD
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202411189644.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The conventional thermoplastic elastomer molded body is difficult to effectively suppress the sound of peeling with glass, and its engagement with other components is insufficient.

Method used

A molded body containing an ethylene-based copolymer, a copolymer derived from an aromatic vinyl compound and a conjugated diene compound, a propylene-based polymer and a lubricant was used. The bending elastic modulus of the molded body was ensured to be 20 MPa or more and 300 MPa or less by a specific composition ratio and process treatment, and the shear strength with the glass measured under specific conditions was 40 N/cm2 or less.

Benefits of technology

It effectively suppresses the peeling sound from glass, and has excellent engagement with other components, meeting the high-performance demands of materials such as automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a thermoplastic elastomer molded body, a composite molded body and a manufacturing method. Provided is a thermoplastic elastomer molded body which is capable of effectively suppressing peeling sound from glass and which has excellent adhesiveness to other members. A molded body containing: at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound; (C) a propylene-based polymer; and (D) a lubricant, in which the flexural modulus at room temperature of the molded body as measured in accordance with JIS K7171 is 20-300 MPa (inclusive), and the shear strength of the molded body with glass as measured under specific conditions is 40 N / cm2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic elastomer molded article. Background Art

[0002] Thermoplastic elastomer molded products are highly recyclable, suitable for injection molding, and excellent in product properties such as strength and flexibility, and therefore are widely used as materials for automobile parts such as glass runs (see, for example, Patent Document 1).

[0003] As the use of thermoplastic elastomer molded products expands, further improvements are required in various performances such as suppression of peeling noise with glass and adhesion with other members.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2021 / 193554 A1 Summary of the invention

[0007] Problems to be solved by the invention

[0008] Under such circumstances, an object of the present invention is to provide a thermoplastic elastomer molded body that can effectively suppress the peeling sound from glass and has excellent bonding properties with other members.

[0009] Means used to solve problems

[0010] The present inventors have conducted intensive studies in view of such background and have completed the present invention as a result.

[0011] That is, the present invention relates to:

[0012] [1] A molded article comprising: at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant, wherein:

[0013] The flexural modulus of the molded article at room temperature measured in accordance with JIS K7171 is 20 MPa or more and 300 MPa or less,

[0014] Two test pieces of length 50 mm×width 6 mm×thickness 2 mm cut out from the molded body were arranged on a flat plate with the 50 mm×2 mm surfaces facing each other at an interval of 60 mm, and the two test pieces were fixed on the flat plate with the 50 mm×6 mm surfaces, so that the other 50 mm×6 mm surfaces of the two test pieces were directly in contact with the 110 mm×110 mm surface of a float plate glass of length 110 mm×width 110 mm×thickness 3 mm according to JIS R 3202, and left to stand at 80° C. for 50 hours, and then the interlayer between the two test pieces and the float plate glass was pulled at 200 mm / min in the shear direction and the length direction of the test pieces, and the shear strength at this time was 40 N / cm 2 the following.

[0015] Hereinafter, [2] to

[14] are each a preferred aspect or embodiment of the present invention.

[0016] [2] The molded article according to [1], wherein the molded article contains (A) an ethylene-based copolymer.

[0017] [3] The molded article according to [2], further comprising (E) mineral oil.

[0018] [4] The molded article according to [3], wherein the (A) ethylene-based copolymer is filled with (E) mineral oil.

[0019] [5] The molded article according to [1], wherein the molded article contains (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound.

[0020] [6] The molded article according to [5], further comprising (E) mineral oil.

[0021] [7] The molded article according to any one of [1] to [6], wherein the (D) lubricant contains at least (D1) monofatty acid amide and (D2) bisfatty acid amide, and the mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide is in the range of 0.2 to 5.

[0022] [8] The molded article according to [7], wherein the mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide is in the range of 0.2 to 1.

[0023] [9] The molded article according to [7] or [8], wherein the (D1) monofatty acid amide is erucamide.

[0024]

[10] The molded article according to any one of [7] to [9], wherein the bisfatty acid amide (D2) is ethylene bisstearyl amide.

[0025]

[11] A method for producing a molded article according to any one of [1] to

[10] , comprising the step of melt-kneading a mixture in the presence of (F) a cross-linking agent, the mixture comprising: (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant.

[0026]

[12] The molded article according to any one of [1] to

[10] , wherein the molded article is an injection molded article.

[0027]

[13] A composite molded body obtained by joining the injection molded body described in

[12] with an extrusion molded body, wherein the extrusion molded body comprises a thermoplastic elastomer composition or a vulcanized rubber composition.

[0028]

[14] The composite molded body according to

[13] , wherein the composite molded body is a glass run channel.

[0029] Effects of the Invention

[0030] According to the present invention, it is possible to provide a molded body which can effectively suppress the peeling sound from glass and has excellent bonding properties with other members. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram showing a method for measuring the shear strength with glass in one embodiment of the present invention. DETAILED DESCRIPTION

[0032] The present invention is a molded article, comprising: at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant, wherein:

[0033] The flexural modulus of the molded article at room temperature measured in accordance with JIS K7171 is 20 MPa or more and 300 MPa or less,

[0034] Two test pieces of length 50 mm×width 6 mm×thickness 2 mm cut out from the molded body were arranged on a flat plate with the 50 mm×2 mm surfaces facing each other at an interval of 60 mm, and the two test pieces were fixed on the flat plate with the 50 mm×6 mm surfaces, so that the other 50 mm×6 mm surfaces of the two test pieces were directly in contact with the 110 mm×110 mm surface of a float plate glass of length 110 mm×width 110 mm×thickness 3 mm according to JIS R 3202, and left to stand at 80° C. for 50 hours, and then the interlayer between the two test pieces and the float plate glass was pulled at 200 mm / min in the shear direction and the length direction of the test pieces, and the shear strength at this time was 40 N / cm 2 the following.

[0035] That is, the molded article of the present invention is a molded article containing at least one component selected from the group consisting of the above-mentioned (A) component and (B) component, (C) component and (D component, a flexural modulus within a specific numerical range, and a shear strength with glass measured under specific conditions within a specific numerical range.

[0036] The molded article of the present invention can contain a thermoplastic elastomer composition by containing at least one component selected from the group consisting of the above-mentioned components (A) and (B), (C) and (D), and can have rubber elasticity after molding and moldability due to thermoplasticity.

[0037] (A) Ethylene copolymers

[0038] The (A) ethylene copolymer constituting the molded article of the present invention is an ethylene copolymer having 50% by mass or more and 99% by mass or less of structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms (wherein the total amount of the ethylene copolymer is 100% by mass). Since it contains 50% by mass or more of structural units derived from ethylene, it is a cross-linkable polymer and is suitable for constituting an island phase of a sea-island structure of a thermoplastic elastomer composition by dynamic cross-linking.

[0039] The (A) ethylene-based copolymer is preferably a random copolymer.

[0040] The (A) ethylene-based copolymer may have a structural unit derived from a monomer other than ethylene and at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms.

[0041] Examples of the α-olefin having a carbon number of 3 or more and 10 or less include propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. In the preparation of the (A) ethylene-based copolymer, the α-olefin having a carbon number of 3 or more and 10 or less may be used alone or in combination of two or more. More preferably, examples of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having a carbon number of 3 or more and 10 or less include a structural unit derived from propylene, a structural unit derived from 1-butene, or a structural unit derived from 1-octene.

[0042] The ratio of the structural unit derived from ethylene in the (A) ethylene-based copolymer is 50% by mass or more and 99% by mass or less, preferably 55% by mass or more and 90% by mass or less, and more preferably 60% by mass or more and 85% by mass or less (wherein the total amount of the (A) ethylene-based copolymer is 100% by mass). The ratio of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having 3 or more and 10 or less carbon atoms in the (A) ethylene-based copolymer is 1% by mass or more and 50% by mass or less, preferably 10% by mass or more and 45% by mass or less, and more preferably 15% by mass or more and 40% by mass or less (wherein the total amount of the (A) ethylene-based copolymer is 100% by mass).

[0043] The ratio of the structural unit derived from ethylene and the ratio of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having a carbon number of 3 or more and 10 or less in the (A) ethylene-based copolymer can be determined by infrared spectroscopy. Specifically, the infrared absorption spectrum of the (A) ethylene-based copolymer can be measured using an infrared spectrophotometer, and the ratio of the structural unit derived from ethylene and the ratio of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having a carbon number of 3 or more and 10 or less can be calculated according to the method described in "Characterization of Polyethylene Based on Infrared Absorption Spectra (Takayama, Usami et al.)" or "Die Makromolekulare Chemie, 177, 461 (1976) (McRae, MA, MadamS, WF et al.)". The ratio of the structural unit derived from ethylene and the ratio of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms in the components (A-1) and (A-2) described below can be determined similarly.

[0044] (A) The ethylene-based copolymer may have a structural unit derived from a monomer other than ethylene and at least one monomer selected from the group consisting of α-olefins having a carbon number of 3 or more and 10 or less. Examples of the other monomers include: conjugated dienes having a carbon number of 4 or more and 8 or less, such as 1,3-butadiene, 2-methyl-1,3-butadiene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene; non-conjugated dienes having a carbon number of 5 or more and 15 or less, such as dicyclopentadiene, 5-ethylidene-2-norbornene, 1,4-hexadiene, 1,5-dicyclooctadiene, 7-methyl-1,6-octadiene, and 5-vinyl-2-norbornene; carboxylic acid vinyl esters such as vinyl acetate; unsaturated carboxylic acid esters such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, and ethyl methacrylate; unsaturated carboxylic acids such as acrylic acid and methacrylic acid; and the like. The other monomer is preferably a non-conjugated diene having 5 to 15 carbon atoms, and more preferably 5-ethylidene-2-norbornene or dicyclopentadiene. The (A) ethylene-based copolymer may contain two or more structural units derived from the other monomer.

[0045] (A) In the case where the ethylene copolymer has a structural unit derived from a monomer other than ethylene and at least one monomer selected from the group consisting of α-olefins having a carbon number of 3 or more and 10 or less, the ratio of the structural unit derived from the other monomer is preferably 30% by mass or less, more preferably 20% by mass or less (wherein the total amount of the (A) ethylene copolymer is set to 100% by mass). The ratio of the structural unit derived from the other monomer can be obtained by infrared spectroscopy. Specifically, the peak intensity of the peak attributed to the other monomer of the (A) ethylene copolymer is measured using an infrared spectrophotometer, and the ratio of the structural unit derived from the other monomer in the (A) ethylene copolymer is calculated from the peak intensity. The ratio of the structural unit derived from the other monomer in the components (A-1) and (A-2) described later can also be obtained in the same manner.

[0046] (A) As ethylene copolymers, there can be mentioned: ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, ethylene-propylene-1-butene copolymers, ethylene-propylene-1-hexene copolymers, ethylene-propylene-1-octene copolymers, ethylene-propylene-5-ethylidene-2-norbornene copolymers, ethylene-propylene-dicyclopentadiene copolymers, ethylene-propylene-1,4-hexadiene copolymers, ethylene-propylene-5-vinyl-2-norbornene copolymers, etc. It can also be an olefin block copolymer comprising a polymer block composed of ethylene and an ethylene-α-olefin copolymer block. The ethylene copolymer as component (A) can be used alone or in combination of two or more. As component (A), ethylene-propylene copolymers or ethylene-propylene-5-ethylidene-2-norbornene copolymers can be preferably used.

[0047] (A) Preferred examples of the ethylene-based copolymer include the following ethylene random copolymer (A-1) and the following ethylene random copolymer (A-2).

[0048] The ethylene random copolymer (A-1) (hereinafter, sometimes referred to as component (A-1)) is an ethylene random copolymer having 50% by mass or more and 90% by mass or less of structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of α-olefins having 3 or more and 10 or less carbon atoms, and having a gel fraction of more than 10% by mass (wherein the total amount of the ethylene random copolymer is 100% by mass). Component (A-1) may have structural units derived from monomers other than ethylene and at least one monomer selected from the group consisting of α-olefins having 3 or more and 10 or less carbon atoms. Specific examples of the α-olefin having 3 to 10 carbon atoms in the component (A-1), the preferred range of the ratio of the structural unit derived from ethylene in the component (A-1), the preferred range of the ratio of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms, specific examples of the structural unit derived from a monomer other than ethylene and at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms, the preferred range of the ratio of the other monomer, and specific examples of the ethylene random copolymer are the same as those for the ethylene-based copolymer (A).

[0049] The more cross-linked structures the ethylene random copolymer has, the larger the gel fraction.

[0050] Component (A-1) can be obtained by crosslinking component (A-2) described below. The gel fraction of component (A-1) can be determined by the following method from the following gel mass of a molded body containing component (A-1) and the mass of component (A-2) contained in the raw material of the molded body.

[0051] The gel fraction of component (A-1) is determined by the method described below using a Soxhlet extractor in which an extraction tube is connected to the lower part of a reflux condenser and a flask is connected to the lower part of the extraction tube. About 1 g of a molded body and an empty mesh cage made of a metal mesh (mesh: 400 mesh) are weighed separately. The mesh cage enclosed in the molded body is introduced into the extraction tube. 300 ml of o-xylene is introduced into the flask. The flask is heated and the o-xylene is refluxed for 24 hours for extraction. After extraction, the mesh cage containing the extraction residue is taken out of the test tube, and the extraction residue is dried under reduced pressure at 100°C using a vacuum dryer, and the mesh cage containing the extraction residue after drying is weighed. The gel mass of the molded body is calculated from the mass difference between the mesh cage containing the extraction residue after drying and the empty mesh cage. The gel fraction (mass %) of component (A-1) is calculated based on the following formula.

[0052] Gel fraction of component (A-1) = (mass of gel in molded product / mass of component (A-2)) × 100

[0053] The gel fraction of the component (A-1) is preferably 20% by mass or more, more preferably 40% by mass or more.

[0054] The more cross-linked structures the ethylene random copolymer has, the larger the gel fraction of the molded body.

[0055] The gel fraction of the molded body can be calculated by the following formula from the gel mass of the molded body obtained by the same method as above.

[0056] Gel fraction of molded body = (mass of gel in molded body / mass of molded body) × 100

[0057] The gel fraction of the molded product is preferably 10% by mass or more and 90% by mass or less, more preferably 15% by mass or more and 60% by mass or less, and still more preferably 18% by mass or more and 40% by mass or less.

[0058] Component (A-1) can be obtained by crosslinking component (A-2) described later. As a method for crosslinking, there can be mentioned a method of melt-kneading a composition containing component (A-2) and a crosslinking agent (F) described later. Crosslinking can be performed simultaneously when producing the molded article of the present invention. In this case, a composition containing component (A-1) and (C) propylene-based polymer can be produced by melt-kneading a composition containing component (A-2), (C) propylene-based polymer described later, and (F) crosslinking agent, as described later.

[0059] The ethylene random copolymer (A-2) (hereinafter, sometimes referred to as component (A-2)) is an ethylene random copolymer having 50% by mass or more and 90% by mass or less of structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of α-olefins having 3 or more and 10 or less carbon atoms, and having a gel fraction of 10% by mass or less (wherein the total amount of the ethylene random copolymer is 100% by mass). Component (A-2) may have structural units derived from monomers other than ethylene and at least one monomer selected from the group consisting of α-olefins having 3 or more and 10 or less carbon atoms. Specific examples of the α-olefin having 3 to 10 carbon atoms in the component (A-2), the preferred range of the ratio of the structural units derived from ethylene in the component (A-2), the preferred range of the ratio of the structural units derived from at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms, specific examples of the structural units derived from monomers other than ethylene and at least one monomer selected from the group consisting of α-olefins having 3 to 10 carbon atoms, the preferred range of the ratio of the other monomers, and specific examples of the ethylene random copolymer are the same as those in the case of the ethylene-based copolymer (A).

[0060] The gel fraction of the component (A-2) is preferably 5% by mass or less, and more preferably 0% by mass. The component (A-2) preferably does not substantially have a crosslinked structure.

[0061] The Mooney viscosity (ML) of the component (A-2) measured at 125°C 1+4 125°C) is preferably 5 or more and 350 or less, more preferably 10 or more and 300 or less, and further preferably 40 or more and 250 or less. It should be noted that the Mooney viscosity (ML 1+ 4125℃) according to JIS K6300, "ML 1+4 "125°C" has the following meanings.

[0062] M: Mooney viscosity

[0063] L: Use large rotor

[0064] 125℃: Measurement temperature

[0065] 1+4: The value measured when the sample is heated for 1 minute and then the rotor is rotated at 2 rpm for 4 minutes

[0066] As a method for producing component (A-2), there can be mentioned a method of copolymerizing ethylene with at least one monomer selected from the group consisting of α-olefins having a carbon number of 3 or more and 10 or less in the presence of a known complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex or a non-metallocene complex. As a polymerization method, there can be mentioned a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, and the like.

[0067] (A1) Ethylene-α-olefin-non-conjugated diene copolymer

[0068] In the (A1) ethylene-α-olefin-non-conjugated diene copolymer preferably used as the (A) ethylene-based copolymer, the ratio of the non-conjugated diene unit is preferably 4% to 15% by weight, and more preferably 6% to 15% by weight. The (A1) ethylene-α-olefin-non-conjugated diene copolymer in the present embodiment is an ethylene-α-olefin-non-conjugated diene copolymer rubber having an A hardness of 85 or less according to JIS K6253.

[0069] As the above-mentioned α-olefin, an α-olefin having 3 to 20 carbon atoms is preferred, and examples thereof include propylene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, and the like; and combinations of two or more thereof. Among them, propylene or 1-butene is preferred from the viewpoint of easy availability, and propylene is more preferred.

[0070] Examples of the non-conjugated diene include chain non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene and 7-methyl-1,6-octadiene; cyclic non-conjugated dienes such as cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene and 6-chloromethyl-5-isopropenyl-2-norbornene; and trienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene and 4-ethylidene-8-methyl-1,7-nonadiene. Among them, 5-ethylidene-2-norbornene or dicyclopentadiene is preferred.

[0071] When the total of the ethylene units, the α-olefin units having 3 to 20 carbon atoms and the non-conjugated diene units contained in the (A1) ethylene-α-olefin-non-conjugated diene copolymer is taken as 100% by mass, the amount of the ethylene units contained in the (A1) ethylene-α-olefin-non-conjugated diene copolymer is usually 30% to 80% by mass, preferably 40% to 80% by mass, and the amount of the α-olefin units having 3 to 20 carbon atoms is usually 5% to 50% by mass, preferably 15% to 45% by mass. The amount of the non-conjugated diene units contained in the (A1) ethylene-α-olefin-non-conjugated diene copolymer is 4% to 15% by mass, preferably 6% to 15% by mass (the total of these three structural units is taken as 100% by mass). Preferred (A1) ethylene-α-olefin-non-conjugated diene copolymers include, specifically, ethylene-propylene-5-ethylidene-2-norbornene copolymers, ethylene-propylene-dicyclopentadiene copolymers, ethylene-propylene-1,4-hexadiene copolymers, and ethylene-propylene-5-vinyl-2-norbornene copolymers, and combinations of two or more thereof. Among them, preferred is an ethylene-propylene-5-ethylidene-2-norbornene copolymer in which the ratio of ethylene units is 40% to 80% by mass, the ratio of propylene units is 15% to 45% by mass, and the ratio of 5-ethylidene-2-norbornene units is 4% to 15% by mass.

[0072] The amounts of ethylene units, α-olefin units having 3 to 20 carbon atoms, and non-conjugated diene units contained in the (A1) ethylene-α-olefin-non-conjugated diene copolymer can be determined by infrared spectroscopy (IR method). Specifically, the (A1) ethylene-α-olefin-non-conjugated diene copolymer is formed into a film having a thickness of about 0.5 mm, and then the peak (1688 cm-1) attributed to 5-ethylidene-2-norbornene of the film is measured using an infrared spectrophotometer. -1 The amount of 5-ethylidene-2-norbornene units in the copolymer was calculated by measuring the absorption peak of the ethylene unit (absorption peak) in the copolymer. Then, the copolymer was formed into a film with a thickness of about 0.1 mm, and the infrared absorption spectrum of the film was measured using an infrared spectrophotometer. The ratio of ethylene units to propylene units was determined according to the method described in the literature (Characterization of polyethylene based on infrared absorption spectrum, written by Takayama, Usami, etc.; or Die Makromolekulare Chemie, 177, 461 (1976) written by McRae, MA, MadamS, WF, etc.). The amount of ethylene units and propylene units can be calculated from the ratio and the amount of 5-ethylidene-2-norbornene units.

[0073] (A1) The ethylene-α-olefin-non-conjugated diene copolymer can be obtained by polymerization using a known method, such as a method of performing polymerization in an inert solvent such as hexane, heptane, toluene, or xylene using a polymerization catalyst such as a Ziegler-Natta catalyst or a metallocene catalyst.

[0074] (A1) Mooney viscosity of ethylene-α-olefin-non-conjugated diene copolymer (ML 1+4 125°C) is preferably 5 or more and 350 or less, more preferably 10 or more and 300 or less, and further preferably 50 or more and 250 or less. The olefin thermoplastic elastomer composition obtained by using the ethylene-α-olefin-non-conjugated diene copolymer (A1) having a Mooney viscosity within the above range can obtain a molded product with excellent mechanical strength and extremely good appearance during molding. The Mooney viscosity (ML 1+4 125℃) is measured according to JIS K6300.

[0075] In addition, when the component (A1) and the mineral oil (hereinafter sometimes referred to as the component (E)) are mixed in advance, the Mooney viscosity (ML) of the component (A1) is 1+4 125°C) can be calculated by the following formula (1).

[0076] log(ML1 / ML2) = 0.0066(ΔPHR) (1)

[0077] ML1: Mooney viscosity of component (A1)

[0078] ML2: Mooney viscosity of the mixture of component (A1) and component (E)

[0079] ΔPHR: Ratio of component (E) to 100 parts by weight of component (A1)

[0080] (B) having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound Copolymers of

[0081] Examples of the copolymer (B) having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound include aromatic vinyl compound-conjugated diene compound polymers, aromatic vinyl compound-conjugated diene compound-aromatic vinyl compound polymers, and hydrogenated products thereof. Among them, hydrogenated products of aromatic vinyl compound-conjugated diene compound-aromatic vinyl compound polymers are preferred.

[0082] Examples of the aromatic vinyl compound in the component (B) include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 1,3-dimethylstyrene, vinylxylene, monochlorostyrene, dichlorostyrene, monobromostyrene, dibromostyrene, ethylstyrene, and vinylnaphthalene, and styrene is preferred.

[0083] Examples of the conjugated diene compound in the component (B) include butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-neopentyl-1,3-butadiene, 2-chloro-1,3-butadiene, and 2-cyano-1,3-butadiene. Butadiene or isoprene is preferred.

[0084] In order to prevent the mold from being easily contaminated during the molding of the molded body, to make the tensile properties and appearance of the molded body good, the ratio of the structural unit derived from the aromatic vinyl compound is preferably 10% by mass or more and 50% by mass or less, more preferably 15% by mass or more and 45% by mass or less, and further preferably 20% by mass or more and 40% by mass or less. Wherein, the total amount of the copolymer having the structural unit derived from the aromatic vinyl compound and the structural unit derived from the conjugated diene compound is set to 100% by mass. It should be noted that the ratio of the structural unit derived from the aromatic vinyl compound can be determined by 1H-NMR.

[0085] The ratio of the structural unit derived from the conjugated diene compound is preferably 50% by mass or more and 90% by mass or less, more preferably 55% by mass or more and 85% by mass or less, and further preferably 60% by mass or more and 80% by mass or less. Wherein, the total amount of the copolymer having the structural unit derived from the aromatic vinyl compound and the structural unit derived from the conjugated diene compound is set to 100% by mass. The ratio of the structural unit derived from the conjugated diene compound can be determined by1H-NMR.

[0086] The component (B) may be a hydrogenated product, in which case the hydrogenation rate is preferably 80% or more, more preferably 90% or more. The hydrogenation rate is a ratio based on a molar basis, with the amount of double bonds in the structural unit derived from the conjugated diene compound in the copolymer before hydrogenation being 100%.

[0087] As a method for producing the component (B), for example, the method described in Japanese Patent Publication No. 40-23798 can be cited. In addition, as a method for hydrogenating a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, for example, the method described in Japanese Patent Publication No. 42-8704, Japanese Patent Publication No. 43-6636, Japanese Patent Publication No. 59-133203, Japanese Patent Publication No. 60-79005 can be cited. As a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, commercial products such as "KRATON-G" manufactured by Kraton Polymer, "SEPTON" manufactured by Kuraray Co., Ltd., "Tuftec" manufactured by Asahi Kasei Corporation, and "TAIPOL" manufactured by TSRC can be used.

[0088] (C) Propylene polymers

[0089] The molded article of the present invention contains (C) a propylene-based polymer.

[0090] The (C) propylene-based polymer (hereinafter sometimes referred to as component (C)) contained in the molded article of the present invention is a propylene (co)polymer having a structural unit derived from propylene in an amount of greater than 50% by mass and less than or equal to 100% by mass. Component (C) may have a structural unit derived from a monomer other than propylene.

[0091] Since component (C) contains more than 50% by mass of structural units derived from propylene, it is a non-crosslinkable or degradable polymer compared with component (A), component (B) and the like, and is suitable for constituting a sea phase of a sea-island structure of a thermoplastic elastomer composition suitable as a material for constituting the molded article of the present invention.

[0092] Examples of the monomer other than propylene include ethylene and α-olefins having 4 or more carbon atoms, and ethylene and α-olefins having 4 or more and 20 or less carbon atoms are preferred.

[0093] Examples of the α-olefin having 4 to 20 carbon atoms include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, and 2,2,4-trimethyl-1-pentene.

[0094] The ratio of structural units derived from propylene, the ratio of structural units derived from ethylene, and the ratio of structural units derived from at least one monomer selected from the group consisting of α-olefins having 4 or more carbon atoms in the (C) propylene-based polymer can be determined by the same method as the ratio of each structural unit in the (A) ethylene-based copolymer.

[0095] Examples of the (C) propylene-based polymer include (C1) propylene homopolymers, propylene random copolymers, and (C2) heterophasic propylene polymers. The molded article of the present invention may contain only one (C) propylene-based polymer or may contain two or more (C) propylene-based polymers.

[0096] Preferred random propylene copolymers include:

[0097] (1) a propylene-ethylene random copolymer in which the ratio of structural units derived from propylene is 90% by mass or more and 99.5% by mass or less and the ratio of structural units derived from ethylene is 0.5% by mass or more and 10% by mass or less (the total amount of structural units derived from propylene and structural units derived from ethylene is taken as 100% by mass);

[0098] (2) a propylene-ethylene-α-olefin random copolymer in which the ratio of structural units derived from propylene is 81% by mass or more and 99% by mass or less, the ratio of structural units derived from ethylene is 0.5% by mass or more and 9.5% by mass or less, and the ratio of structural units derived from α-olefins having 4 to 10 carbon atoms is 0.5% by mass or more and 9.5% by mass or less (the total amount of structural units derived from propylene, structural units derived from ethylene and structural units derived from α-olefins having 4 to 10 carbon atoms is 100% by mass);

[0099] (3) A propylene-α-olefin random copolymer in which the ratio of structural units derived from propylene is 90% by mass or more and 99.5% by mass or less, and the ratio of structural units derived from α-olefins having 4 to 10 carbon atoms is 0.5% by mass or more and 10% by mass or less (wherein the total amount of structural units derived from propylene and structural units derived from α-olefins having 4 to 10 carbon atoms is 100% by mass).

[0100] Examples of the α-olefins having 4 to 10 carbon atoms in (1) and (2) above include linear α-olefins such as 1-butene, 1-pentene, 1-hexene, 1-octene, and 1-decene; and branched α-olefins such as 3-methyl-1-butene and 3-methyl-1-pentene. In the preparation of (1) and (2) above, the α-olefins having 4 to 10 carbon atoms may be used alone or in combination of two or more.

[0101] The method for producing the (C1) propylene homopolymer and propylene random copolymer includes a method of polymerizing propylene (and other monomers as required) in the presence of a Ziegler-Natta catalyst or a complex catalyst such as a metallocene complex or a non-metallocene complex. The polymerization method includes a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, and the like.

[0102] In the present specification, the term "heterophasic propylene polymer material" refers to a mixture having the following structure: a copolymer (II) having 20% ​​to 90% by mass of structural units derived from ethylene and structural units derived from at least one monomer selected from the group consisting of α-olefins having 3 or more carbon atoms (wherein the total mass of the copolymer is set to 100% by mass) (hereinafter sometimes referred to as "copolymer (II)") is dispersed in a matrix of a polymer (I) having 80% to 100% by mass of structural units derived from propylene (wherein the total mass of the polymer is set to 100% by mass) (hereinafter sometimes referred to as "polymer (I)").

[0103] In the heterophasic propylene polymer material (C2) as the component (C), when the total amount of the heterophasic propylene polymer material is taken as 100% by mass, the structural units derived from propylene account for 50% by mass or more.

[0104] The amount of polymer (I) contained in the heterophasic propylene polymer material (C2) is preferably from 70% by mass to 90% by mass, more preferably from 75% by mass to 90% by mass (wherein the total amount of the heterophasic propylene polymer material (C2) is taken as 100% by mass). The amount of copolymer (II) contained in the heterophasic propylene polymer material (C2) is preferably from 10% by mass to 30% by mass, more preferably from 10% by mass to 25% by mass (wherein the total amount of the heterophasic propylene polymer material (C2) is taken as 100% by mass).

[0105] Examples of the α-olefin having 3 or more carbon atoms in the copolymer (II) include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 2-ethyl-1-hexene, 2,2,4-trimethyl-1-pentene, etc. The α-olefin having 3 or more carbon atoms is preferably an α-olefin having 3 or more carbon atoms and 20 or less carbon atoms, more preferably an α-olefin having 3 or more carbon atoms and 10 or less carbon atoms, and further preferably propylene, 1-butene, 1-hexene, or 1-octene. In the copolymer (II), the α-olefin having 3 or more carbon atoms may be used alone or in combination of two or more.

[0106] The ratio of the structural unit derived from ethylene contained in the copolymer (II) is preferably 22% by mass or more and 80% by mass or less, more preferably 25% by mass or more and 70% by mass or less, and further preferably 27% by mass or more and 60% by mass or less (wherein the total amount of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having 3 or more carbon atoms and the structural unit derived from ethylene is taken as 100% by mass). The ratio of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having 3 or more carbon atoms contained in the copolymer (II) is preferably 20% by mass or more and 78% by mass or less, more preferably 30% by mass or more and 75% by mass or less, and further preferably 40% by mass or more and 73% by mass or less (wherein the total amount of the structural unit derived from at least one monomer selected from the group consisting of α-olefins having 3 or more carbon atoms and the structural unit derived from ethylene is taken as 100% by mass).

[0107] Examples of the copolymer (II) include propylene-ethylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, propylene-ethylene-1-butene copolymers, propylene-ethylene-1-hexene copolymers, propylene-ethylene-1-octene copolymers, etc., preferably propylene-ethylene copolymers or propylene-ethylene-1-butene copolymers. The copolymer (II) is usually a random copolymer.

[0108] Regarding the method for producing the (C2) heterophasic propylene polymer material as component (C), there can be mentioned a method of polymerizing monomers including propylene and ethylene in multiple stages in the presence of a polymerization catalyst. For example, there can be mentioned a method of using a polymerization catalyst to polymerize monomers containing propylene in the presence of a polymerization catalyst in a first polymerization step to produce a polymer (I), and in a second polymerization step, copolymerizing ethylene with at least one monomer selected from the group consisting of α-olefins having 3 or more carbon atoms in the presence of the polymer (I) obtained in the first polymerization step to produce a copolymer (II). As the polymerization catalyst used in the production of the (C2) heterophasic propylene polymer material, there can be mentioned, for example, a Ziegler catalyst, a Ziegler-Natta catalyst; a catalyst comprising a transition metal compound of the fourth group of the periodic table having a cyclopentadienyl ring and an alkylaluminoxane; a catalyst comprising a transition metal compound of the fourth group of the periodic table having a cyclopentadienyl ring, a compound that forms an ionic complex by reacting with the transition metal compound, and an organic aluminum compound, etc. In addition, a prepolymerization catalyst can be used in the presence of the above-mentioned polymerization catalyst. Examples of the prepolymerization catalyst include catalysts described in JP-A Nos. 61-218606, 61-287904, 5-194685, 7-216017, 9-316147, 10-212319, and 2004-182981.

[0109] Regarding the polymerization method in the production of the (C2) heterophasic propylene polymer material as component (C), examples include: bulk polymerization, solution polymerization, slurry polymerization, gas phase polymerization, etc. Examples of inert hydrocarbon solvents used in solution polymerization and slurry polymerization include: propane, butane, isobutane, pentane, hexane, heptane, octane, etc. These polymerization methods can be combined in two or more, and can be either intermittent or continuous. As the polymerization method in the production of the (C2) heterophasic propylene polymer material, continuous gas phase polymerization, bulk-gas phase polymerization in which bulk polymerization and gas phase polymerization are continuously performed is preferred.

[0110] From the viewpoint of adhesion with other members, the melt flow rate (MFR) of the (C) propylene-based polymer measured under the conditions of a temperature of 230° C. and a load of 21.18 N in accordance with JIS K7210 is preferably 0.3 (g / 10 min) or more and 200 (g / 10 min) or less. The melt flow rate of the (C) propylene-based polymer is more preferably 2.5 (g / 10 min) or more and 150 (g / 10 min) or less, and further preferably 10 (g / 10 min) or more and 105 (g / 10 min) or less.

[0111] (C) Intrinsic viscosity (hereinafter referred to as [η cxis ]) is preferably from 0.1 dl / g to 6.0 dl / g, more preferably from 0.3 dl / g to 5.0 dl / g, and further preferably from 0.3 dl / g to 3.1 dl / g.

[0112] The intrinsic viscosity can be determined by the following procedure: The reduced viscosity is measured in tetralin at 135° C. using an Ubbelohde viscometer, and the intrinsic viscosity is determined by extrapolation from the reduced viscosity according to the calculation method described in “Polymer Solutions, Polymer Experiments 11” (published by Kyoritsu Publishing Co., Ltd. in 1982), page 491.

[0113] Here, the CXS part and the CXIS part are obtained by the following method. About 5 g of (C) propylene polymer is completely dissolved in 500 ml of boiling xylene. The obtained xylene solution is slowly cooled to 20°C, conditioned at 20°C for more than 4 hours, and the precipitate is separated from the solution by filtration. The precipitate is the CXIS part. It should be noted that the substance obtained by removing the solvent from the solution is the 20°C xylene soluble part (CXS part).

[0114] The (C) propylene-based polymer is preferably a (C1) propylene homopolymer, a propylene-ethylene random copolymer, a propylene-ethylene-butene random copolymer or a (C2) heterophasic propylene polymer material, more preferably a (C1) propylene homopolymer or a (C2) heterophasic propylene polymer material, further preferably a (C1) propylene homopolymer.

[0115] (D) Lubricant

[0116] The lubricant (D) is not particularly limited, and various compounds that have been conventionally used as lubricants in the technical field can be appropriately used. Specific examples include hydrocarbon lubricants, fatty acid lubricants, fatty acid amide lubricants, ester lubricants, alcohol lubricants, metal soap lubricants, silicone oils, silicone rubbers and other organic silicon lubricants, inorganic lubricants, etc., but are not limited thereto.

[0117] Among them, fatty acid amide-based lubricants are preferably used, and higher fatty acid amides are particularly preferably used.

[0118] The fatty acid amide-based lubricant is not particularly limited, and conventionally known compounds can be used.

[0119] As the fatty acid constituting the fatty acid amide, a higher fatty acid is preferred. Examples of the higher fatty acid include fatty acids having 6 or more, preferably 12 or more, and preferably 24 or less carbon atoms (the carbon atom number is the carbon atom number of the higher fatty acid, not the carbon atom number of the fatty acid amide as component (D) as a whole; for example, the carbon atom number of the bisfatty acid amide described later is about twice the above-mentioned carbon atom number).

[0120] The fatty acid amide may be used alone or in combination of two or more.

[0121] Preferred fatty acid amides include (D1) monofatty acid amides and (D2) bisfatty acid amides.

[0122] The amount of the fatty acid amide lubricant is not particularly limited, but is preferably 0.05 to 5 parts by mass, more preferably 0.24 parts by mass or more, further preferably 1.2 parts by mass or more, more preferably 3.0 parts by mass or less, further preferably 1.8 parts by mass or less, relative to 100 parts by mass of the total of components (A) to (C).

[0123] When the amount of the fatty acid amide lubricant is greater than or equal to the lower limit, it is preferred from the perspective of suppressing the intended peeling sound, etc. When the amount of the fatty acid amide lubricant is less than or equal to the upper limit, it is preferred from the perspective of suppressing the appearance defect caused by bleeding, etc.

[0124] (D1) Mono fatty acid amide

[0125] The (D1) monofatty acid amide may be an amide formed from one fatty acid and one amine, and no other restrictions are particularly applied. The (D1) monofatty acid amide may be a saturated fatty acid amide or an unsaturated fatty acid amide.

[0126] Here, as the saturated fatty acid constituting the monofatty acid amide (D1), a saturated fatty acid having 6 to 25 carbon atoms is preferred, and examples thereof include caproic acid, heptanoic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, arachidic acid, heneicosanoic acid, behenic acid, and lignoceric acid.

[0127] The unsaturated fatty acid constituting the monofatty acid amide (D1) is preferably an unsaturated fatty acid having 6 to 25 carbon atoms, and examples thereof include erucic acid, oleic acid, myristic acid, palmitoleic acid, cis-6-hexadecenoic acid, trans-11-octadecenoic acid, cis-9-eicosenoic acid, eicosenoic acid, nervonic acid, linoleic acid, eicosadienoic acid, docosadienoic acid, linolenic acid, pinolenic acid, eleostearic acid, mead acid, dihomoic acid, and succinic acid. -γ-linolenic acid, eicosatrienoic acid, octadecatetraenoic acid, arachidonic acid, eicosatetraenoic acid, docosatetraenoic acid, octadecatoneoic acid, eicosapentaenoic acid, all-cis-4,7,10,13,16-docosapentaenoic acid, all-cis-7,10,13,16,19-docosapentaenoic acid, tetracosapentaenoic acid, docosahexaenoic acid, tetracosahexoneoic acid, brassoneoic acid, elaidic acid, ricinoleic acid.

[0128] Among the monofatty acid amides (D1) formed from these, erucamide and oleamide are preferred, and erucamide is particularly preferred.

[0129] The amount of the monofatty acid amide (D1) is not particularly limited, but is preferably 0.05 to 3 parts by mass, more preferably 0.08 parts by mass or more, further preferably 0.4 parts by mass or more, more preferably 1.8 parts by mass or less, further preferably 0.6 parts by mass or less, relative to 100 parts by mass of the total of components (A) to (C).

[0130] When the amount of the monofatty acid amide (D1) is equal to or greater than the above lower limit, it is preferred from the perspective of suppressing the intended peeling sound, etc. When the amount of the monofatty acid amide (D1) is equal to or less than the above upper limit, it is preferred from the perspective of suppressing the appearance defect caused by bleeding, etc.

[0131] The molecular weight of the monofatty acid amide (D1) is not particularly limited, but is preferably 101 to 499, more preferably 201 to 449, and even more preferably 251 to 399. When the molecular weight of the monofatty acid amide (D1) is within this range, it is preferred from the perspective of suppressing peeling noise and poor appearance due to bleeding.

[0132] (D2) Bis-fatty acid amide

[0133] The (D2) bis fatty acid amide is not particularly limited as long as it is an amide formed from two fatty acids and one diamine. The (D2) bis fatty acid amide may be a di-saturated fatty acid amide or a di-unsaturated fatty acid amide.

[0134] Preferred examples of the bisfatty acid amide (D2) include methylenebisaturated fatty acid amide, methylenebisunsaturated fatty acid amide, ethylenebisaturated fatty acid amide, and ethylenebisunsaturated fatty acid amide. Here, specific examples of the saturated fatty acid and the unsaturated fatty acid constituting the bisfatty acid amide (D2) are the same as those described above for the monofatty acid amide (D1). The two fatty acids in the bisfatty acid amide (D2) may be of the same type, that is, two fatty acids of the same type may be used, or two different fatty acids may be used in combination.

[0135] Among them, ethylene bisstearamide and ethylene bisoleamide are preferred, and ethylene bisstearamide is particularly preferred.

[0136] The amount of the bis fatty acid amide (D2) is not particularly limited, but is preferably 0.05 to 3 parts by mass, more preferably 0.16 parts by mass or more, further preferably 0.8 parts by mass or more, further preferably 1.8 parts by mass or less, further preferably 1.2 parts by mass or less, relative to 100 parts by mass of the total of components (A) to (C).

[0137] When the amount of the bisfatty acid amide (D2) is equal to or greater than the lower limit, it is preferred from the perspective of suppressing the intended peeling sound, etc. When the amount of the bisfatty acid amide (D2) is equal to or less than the upper limit, it is preferred from the perspective of suppressing the appearance defect caused by bleeding, etc.

[0138] The molecular weight of the bisfatty acid amide (D2) is not particularly limited, but is preferably 200 to 999, more preferably 450 to 849, and even more preferably 500 to 799. When the molecular weight of the bisfatty acid amide (D2) is within this range, it is preferred from the perspective of suppressing the intended peeling sound and the appearance defect caused by bleeding.

[0139] As the lubricant (D), it is preferred to use (D1) a monofatty acid amide and (D2) a bisfatty acid amide in combination. That is, it is preferred that the lubricant (D) contains at least (D1) a monofatty acid amide and (D2) a bisfatty acid amide.

[0140] By using (D1) monofatty acid amide and (D2) bisfatty acid amide in combination, the molded article of the present embodiment can more effectively suppress the peeling sound from the glass and can also have more excellent bonding properties with other members.

[0141] When (D1) monofatty acid amide and (D2) bisfatty acid amide are used in combination, the mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide is not particularly limited, but is preferably in the range of 0.2 to 5, particularly preferably in the range of 0.2 to 1, and further preferably in the range of 0.4 to 0.6.

[0142] When the mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide is within the range of 0.2 to 5, the molded article of the present embodiment can more effectively suppress the peeling sound from the glass and can further improve the bonding property with other members.

[0143] In the present embodiment, by using (D1) monofatty acid amide and (D2) bisfatty acid amide in combination and setting the mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide in the range of 0.2 to 5, the mechanism by which the peeling sound from the glass can be more effectively suppressed and the bonding properties with other components can be improved is not necessarily clear, but it is presumed that there is a certain relationship between the affinity between the (D1) monofatty acid amide and the glass surface having a large number of polar groups being improved via the (D2) bisfatty acid amide having two amide groups.

[0144] (E) Mineral oil

[0145] The molded article of the present invention may contain (E) mineral oil.

[0146] (E) mineral oil may be mixed with (A) ethylene-based copolymer or (B) copolymer having structural units derived from an aromatic vinyl compound and structural units derived from a conjugated diene compound, that is, (A) ethylene-based copolymer and / or (B) copolymer having structural units derived from an aromatic vinyl compound and structural units derived from a conjugated diene compound may be filled with (E) mineral oil.

[0147] Examples of the (E) mineral oil preferably used as a softener in the present embodiment include high boiling point fractions of petroleum such as aromatic mineral oil, naphthenic mineral oil and paraffinic mineral oil (average molecular weight of 300 to 1500 and pour point of 0° C. or less). Among them, paraffinic mineral oil is preferred.

[0148] The (E) mineral oil is preferably added as an extender oil to the (A) ethylene copolymer, particularly preferably the (A1) ethylene-α-olefin-non-conjugated diene copolymer, or the (B) copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound. The method of adding the mineral oil may be a known method, for example: (1) a method of mechanically kneading the two using a kneading device such as a roll or a Banbury mixer; (2) a method of adding the component (E) to a solution of the component (A) or (B) prepared in a liquid state, followed by desolvation by a method such as steam stripping.

[0149] When (E) a mineral oil is blended as an extender oil for (A) an ethylene-based copolymer or (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, the Mooney viscosity (ML) of the composition (oil-extended polymer) comprising (E) the mineral oil and (A) an ethylene-based copolymer and / or (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound measured at 125°C is: 1+4 125°C) is preferably 5 or more and 300 or less, more preferably 10 or more and 250 or less, and further preferably 40 or more and 200 or less. It should be noted that the Mooney viscosity (ML 1+4 125℃) is measured according to JIS K6300.

[0150] From the viewpoint of achieving the above-mentioned Mooney viscosity, etc., when the total amount of (A) the ethylene-based copolymer and / or (B) the copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound and (E) the mineral oil is 100 parts by mass, the amount of the (E) mineral oil added is preferably 20 to 80 parts by mass, more preferably 25 to 70 parts by mass, and even more preferably 30 to 60 parts by mass.

[0151] (F) Cross-linking agent

[0152] The molded article of the present invention is preferably a thermoplastic elastomer composition having a sea-island structure. To this end, the molded article is preferably produced by melt-kneading a mixture containing at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant in the presence of (F) a cross-linking agent.

[0153] As the crosslinking agent (F) preferably used in the present embodiment, a crosslinking agent commonly used in the crosslinking of rubber can be used, and examples thereof include organic peroxides, phenolic resins, sulfur, sulfur-containing compounds, p-benzoquinone, derivatives of p-benzoquinone dioxime, bismaleimide compounds, epoxy compounds, silane compounds, and amino resins. Among them, organic peroxides and phenolic resins are preferred.

[0154] Examples of the organic peroxide include ketone peroxides, diacyl peroxides, hydroperoxides, dialkyl peroxides, peroxyketals, alkyl peresters, percarbonates, peroxydicarbonates, and peroxyesters.

[0155] Specific examples of the organic peroxide include diisopropylbenzene peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne, 1,3-bis(tert-butylperoxyisopropyl)benzene, tert-butylcumyl peroxide, di-tert-butyl peroxide, 2,2,4-trimethylpentyl-2-hydroperoxide, diisopropylbenzene hydroperoxide, isopropylbenzene peroxide, tert-butyl peroxide, 1,1-di(tert-butylperoxy)-3,5,5-trimethylcyclohexane, 1,1-di-tert-butylperoxycyclohexane, isobutyl peroxide, 2,4-dichlorobenzoyl peroxide, o-methylbenzoyl peroxide, bis-3,5,5-trimethylhexanoyl peroxide, lauroyl peroxide, benzoyl peroxide, and p-chlorobenzoyl peroxide.

[0156] The organic peroxide may be used alone or in combination of two or more.

[0157] The organic peroxide used in the present embodiment can be in any form such as liquid, powder, granule, etc. In addition, in order to make the dispersibility good, the organic peroxide is more preferably used after being diluted with a diluent such as an inorganic filler, mineral oil, solvent, etc. that is inert to the cross-linking reaction. In addition, its addition method is also more preferably added in a liquid state. Among them, paraffin-based oil is a preferred diluent in consideration of its operability and the influence on the product.

[0158] In order to make the crosslinking reaction proceed evenly and slowly, an organic peroxide can be used in combination with a crosslinking aid. As a crosslinking aid, polyfunctional compounds such as sulfur, methacrylates, and maleimides can be used. As a crosslinking aid, examples include sulfur, p-benzoquinone dioxime, p-, p-dibenzoylbenzoquinone dioxime, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, diallyl phthalate, tetraallyloxyethane, triallyl isocyanurate, N,N'-m-phenylene bismaleimide, maleic anhydride, divinylbenzene, zinc diacrylate, and zinc dimethacrylate. Among them, N,N'-m-phenylenebismaleimide, p,p'-dibenzoylbenzoquinonedioxime, divinylbenzene, trimethylolpropane trimethacrylate or triallyl isocyanurate are preferred. N,N'-m-phenylenebismaleimide can also be used alone as a crosslinking agent.

[0159] Examples of the phenolic resin used as the crosslinking agent (F) include compounds represented by the following formula that are generally used as crosslinking agents for rubber (see U.S. Pat. Nos. 3,287,440 and 3,709,840):

[0160]

[0161] In the formula, n is an integer of 0 to 10; X and Y are each independently a hydroxyl group, a halogenated alkyl group or a halogen atom; and R is a saturated hydrocarbon group having 1 to 15 carbon atoms. The compound can be produced by polycondensing a substituted phenol and an aldehyde using a base catalyst.

[0162] Examples of the phenolic resin include alkylphenol formaldehyde resins and brominated alkylphenol formaldehyde resins.

[0163] When a phenolic resin is used as a crosslinking agent, it may be combined with a crosslinking accelerator in order to adjust the speed of the crosslinking reaction. Examples of the crosslinking accelerator include metal halides such as stannous chloride and ferric chloride, and organic halides such as chlorinated polypropylene, brominated butyl rubber, and chloroprene rubber.

[0164] The phenolic resin is preferably used in combination with a dispersant such as a metal oxide (eg, zinc oxide) and stearic acid.

[0165] There is no particular limitation on the amount of the cross-linking agent (F) added, and a person skilled in the art can appropriately set the amount of the cross-linking agent (F) added so as to be suitable for cross-linking the (A) ethylene-based copolymer, the (B) copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, and the like at a desired level.

[0166] The (F) cross-linking agent may be decomposed in a process such as melt kneading for cross-linking (A) the ethylene-based copolymer, (B) the copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, etc. Therefore, the suitable amount of the (F) cross-linking agent is usually not specified by the amount of the (F) cross-linking agent remaining in the molded article of the present invention, but by the amount of the (F) cross-linking agent before melt kneading (A) the ethylene-based copolymer, (B) the copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, and (C) the propylene-based polymer in the presence of the (F) cross-linking agent.

[0167] The amount of the cross-linking agent (F) before melt-kneading is preferably 0.001 part by mass or more and 3.0 parts by mass or less, more preferably 0.01 part by mass or more and 2.0 parts by mass or less, and even more preferably 0.1 part by mass or more and 1.0 part by mass or less, relative to 100 parts by mass of the total amount of (A) the ethylene-based copolymer, (B) the copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, and (C) the propylene-based polymer.

[0168] When a crosslinking aid is used together with the crosslinking agent (F), the amount of the crosslinking aid before melt-kneading is preferably 0.01 parts by mass or more and 10 parts by mass or less, and more preferably 0.05 parts by mass or more and 1.0 parts by mass or less, relative to 100 parts by mass of the total amount of (A) the ethylene-based copolymer, (B) the copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, and (C) the propylene-based polymer.

[0169] Other Ingredients

[0170] The molded article of the present invention may contain various additives in addition to at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound as essential components, (C) a propylene-based polymer and (D) a lubricant, and the above-mentioned preferred components (E) mineral oil and (F) a crosslinking agent.

[0171] The additives may include, for example, polymers or oligomers other than the above-mentioned components (A) to (C), softeners other than the mineral oil (E), inorganic fillers (talc, calcium carbonate, calcined kaolin, glass fiber, hollow glass spheres, silica, metal soap, titanium dioxide, mica, potassium titanate fiber, carbon black, etc.), organic fillers (fibers, wood powder, cellulose powder, carbon fiber, etc.), antioxidants (phenols, sulfur, phosphorus, lactones, vitamins, etc.), weathering stabilizers, ultraviolet absorbers (benzotriazoles, triazines, anilides, benzophenones, etc.) ), heat stabilizers, light stabilizers (hindered amines, benzoates, etc.), pigments (inorganic pigments, organic pigments, pigment dispersants, etc.), nucleating agents, foaming agents, foaming nucleating agents, plasticizers, flame retardants, brighteners, antibacterial agents, light diffusers, adsorbents (metal oxides (zinc oxide, magnesium oxide, etc.), wetting dispersants, VOC / odor removers, water storage agents (aqueous media containing amphiphilic polymers, etc.), scratch resistance enhancers, metal chlorides (ferric chloride, calcium chloride, etc.), hydrotalcites, aluminates, etc. These additives can be used alone or in combination of two or more.

[0172] Examples of resins other than components (A) to (C) include olefin resins (excluding components (A) and (C)), olefin elastomers (excluding components (A) and (C)), polyphenylene ether resins, polyamide resins, polyester resins, polyoxymethylene resins, polymethyl methacrylate resins, and the like.

[0173] The thermoplastic elastomer molded article of the present invention may be a molded article containing carbon 14 (14C) as a constituent element, or may be a molded article obtained by material recycling (mechanical recycling).

[0174] The concentration of carbon 14 (14C) contained in the thermoplastic elastomer molded product is determined as pMC (modern carbon percentage: unit %) by the AMS (accelerator mass spectrometry) method specified in ISO 16620-2:2019.

[0175] It is known that carbon 14 (14C) is contained in carbon dioxide in the atmosphere at a certain ratio, and therefore plants such as corn and trees that grow by absorbing carbon dioxide in the atmosphere contain 14C. In addition, it is also known that fossil resources such as petroleum, which are believed to be stored underground for a long time, contain almost no carbon 14 (14C). Therefore, by using plant-derived substances in the raw materials of monomers of component (A) ethylene copolymer, component (B) copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, component (C) propylene polymer and / or component (E) mineral oil used for the thermoplastic elastomer molded body, carbon 14 (14C) can be contained in the constituent elements of the thermoplastic elastomer.

[0176] In the production of the component (A) ethylene-based copolymer, the component (B) copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, the component (C) propylene-based polymer and / or the component (E) mineral oil for use in the thermoplastic elastomer molded product, monomers derived from fossil resources (ethylene, propylene, 1-butene, 1-hexene, etc.), monomers derived from plants (ethylene, propylene, 1-butene, 1-hexene, etc.), chemically recovered monomers (ethylene, propylene, 1-butene, 1-hexene, etc.), etc. can be used, and two or more of them can be used in combination.

[0177] Specific examples of combinations of monomers include: ethylene derived from fossil resources / ethylene derived from plants / chemically recovered ethylene, propylene derived from fossil resources / propylene derived from plants / chemically recovered propylene, propylene derived from fossil resources / propylene derived from plants / chemically recovered propylene / ethylene derived from fossil resources / ethylene derived from plants / chemically recovered ethylene.

[0178] Monomers derived from fossil resources are derived from carbon in the form of underground resources such as petroleum, coal, and natural gas, and generally contain almost no carbon 14 (14C). Examples of methods for producing monomers derived from fossil resources include well-known methods such as methods for producing olefins by cracking naphtha / ethane derived from petroleum, dehydrogenation of ethane / propane, etc.

[0179] Plant-derived monomers are derived from carbon that circulates on the earth's surface in the form of plants and animals, and usually contain a certain ratio of carbon 14 (14C). Examples of methods for producing plant-derived monomers include known methods, such as cracking of bio-naphtha / vegetable oil / animal oil, dehydrogenation of bio-propane, etc., separation of alcohol from fermentation products of sugars extracted from plant raw materials such as sugarcane or corn, and dehydration reaction of the alcohol (Japanese Patent Publication Nos. 2010-511634, 2011-506628, 2013-503647, etc.), and metathesis reaction of ethylene obtained from plant-derived ethanol with n-butene (WO2007 / 055361, etc.).

[0180] Chemically recycled monomers are derived from carbon produced by the decomposition or combustion of waste, and the amount of carbon 14 (14C) they contain varies depending on the waste. As methods for producing chemically recycled monomers, known methods can be cited, for example, methods for thermally decomposing waste plastics (Japanese Patent Publication No. 2017-512246, etc.); methods for cracking waste vegetable oils, waste animal oils, etc. (Japanese Patent Publication No. 2018-522087, etc.); methods for gasifying, alcoholizing, and dehydrating waste such as kitchen waste, biomass waste, food waste, waste oil, waste wood, waste paper, and waste plastics (Japanese Patent Publication No. 2019-167424, WO2021 / 006245, etc.).

[0181] When two or more olefins derived from fossil resources, olefins derived from plants, and chemically recovered olefins are used, the olefins produced separately can be mixed in a combination of olefins derived from fossil resources / olefins derived from plants, olefins derived from fossil resources / chemically recovered olefins, olefins derived from plants / chemically recovered olefins, olefins derived from fossil resources / olefins derived from plants / chemically recovered olefins. In addition, a substance produced in the form of a mixture of the above-mentioned olefin combinations by using a mixture of a combination of a compound derived from fossil resources / a compound derived from plants, a compound derived from fossil resources / chemically recovered compounds, a compound derived from plants / chemically recovered compounds, a compound derived from fossil resources / a compound derived from plants / chemically recovered compounds in the raw materials / manufacturing intermediates of the olefin manufacturing process can also be used.

[0182] As the component (A) ethylene copolymer containing carbon 14 (14C), commercially available ethylene copolymers and ethylene polymers having more than 90% by mass of monomer units derived from ethylene can be used, for example, the "I'M GREEN" series manufactured by Braskem, the "TRUCIRCLE" series manufactured by SABIC, the "CirculenRenew" series manufactured by LyondellBasell, etc.

[0183] As the component (C) propylene polymer containing carbon 14 (14C), commercially available propylene polymers can be used, for example, "Bornewables" series manufactured by Borealis, "TRUCIRCLE" series manufactured by SABIC, "CirculenRenew" series manufactured by LyondellBasell, and the like.

[0184] From the viewpoint of reducing environmental load, the carbon 14 (14C) concentration of the thermoplastic elastomer molded product is preferably 0.2 pMC% or more, more preferably 0.5 pMC% or more, further preferably 1 pMC% or more, further preferably 5 pMC% or more, and particularly preferably 10 pMC% or more. From the viewpoint of cost, the carbon 14 (14C) concentration of the thermoplastic elastomer molded product is preferably 99 pMC% or less, more preferably 95 pMC% or less, further preferably 90 pMC% or less, further preferably 70 pMC% or less, and particularly preferably 50 pMC% or less.

[0185] The carbon 14 (14C) concentration of the thermoplastic elastomer molded product can be adjusted by changing the ratio of the fossil resource-derived olefin, the plant-derived olefin, and the chemically recovered olefin used for producing the thermoplastic elastomer molded product.

[0186] Molded body

[0187] The molded article of the present invention may contain at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant. The amount of each component blended is not particularly limited. When the total of the components (A) to (C) is 100 parts by mass, it is preferred that the molded article contain a total of 40 to 85 parts by mass of the (A) ethylene-based copolymer and / or (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, and 15 to 60 parts by mass of the (C) propylene-based polymer.

[0188] The total amount of (A) the ethylene copolymer and / or (B) the copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound is more preferably 50 to 90% by mass, particularly preferably 55 to 85% by mass.

[0189] The amount of the propylene polymer (C) is more preferably 10 to 50% by mass, particularly preferably 15 to 45% by mass. With such a ratio, the molded article of the present embodiment can further improve various properties such as suppression of peeling sound from glass and adhesion to other members.

[0190] The flexural modulus of the molded article of the present invention at room temperature measured in accordance with JIS K7171 is 20 MPa or more and 300 MPa or less.

[0191] When the flexural modulus is within the above range, combined with the other requirements of the present invention, the molded article of the present invention can achieve technical effects such as flexibility and shape retention.

[0192] More specifically, from the viewpoint of shape retainability and the like, the flexural modulus of the molded article is preferably 20 MPa or more.

[0193] From these viewpoints, the flexural modulus of the molded article of the present invention is preferably 40 MPa or more, more preferably 50 MPa or more.

[0194] More specifically, from the viewpoint of flexibility and the like, the flexural modulus of the molded article is preferably 300 MPa or less.

[0195] From these viewpoints, the flexural modulus of the molded article of the present invention is preferably 200 MPa or less, more preferably 100 MPa or less.

[0196] The flexural modulus of the molded article can be measured in accordance with JIS K7171, and more specifically, for example, can be measured in accordance with the method described in Examples of the present application.

[0197] The flexural modulus of the molded article can be appropriately adjusted by selecting and adjusting the materials and / or blending amounts of the components constituting the molded article, particularly the components (A) to (C), adjusting the degree of crosslinking when a crosslinking agent (F) is used, changing the melt kneading conditions, etc.

[0198] The shear strength between the molded article of the present invention and the float glass measured under specific conditions, more specifically, the following shear strength is 40 N / cm 2As follows: Two test pieces of length 50 mm×width 6 mm×thickness 2 mm cut out from the molded body of the present invention are arranged on a flat plate in such a manner that the interval between the opposing 50 mm×2 mm surfaces is 60 mm, and the two test pieces are fixed to the flat plate at the 50 mm×6 mm surfaces, so that the other 50 mm×6 mm surfaces of the two test pieces are directly in contact with the 110 mm×110 mm surface of a float plate glass having a length of 110 mm×width 110 mm×thickness 3 mm according to JIS R 3202, and the two test pieces are allowed to stand at 80° C. for 50 hours, and then the shear strength of the interlayer between the two test pieces and the float plate glass when pulled at 200 mm / min in the shear direction and in the length (50 mm) direction of the test pieces.

[0199] The shear strength between the glass and the float glass measured under the above specific conditions is 40N / cm 2 Next, in combination with other conditions of the present invention, the molded article of the present invention can achieve significant technical effects having high practical value, such as being able to effectively suppress the peeling sound from the glass and being excellent in bonding properties with other members.

[0200] The shear strength between the glass and the float glass measured under the above specific conditions is 40N / cm 2 The mechanism by which the above-mentioned technical effects can be achieved may not be clear, but it is presumed to be related to the following matters, etc.: the shear strength between the glass and the peeling sound with the glass are properties that may be affected by the state of the glass / molded body interface, and the interface state that can effectively suppress the peeling sound can be indirectly evaluated by the shear strength.

[0201] The shear strength between the glass and the float glass measured under the above-mentioned specific conditions is preferably 30 N / cm 2 Below, particularly preferably 14N / cm 2 Below, more preferably 9N / cm 2 the following.

[0202] There is no particular lower limit to the shear strength with float glass measured under the above-mentioned specific conditions, but from the viewpoint of adhesion with glass, etc., it is preferably 0.1 N / cm 2 Above, particularly preferably 1N / cm 2 above.

[0203] The shear strength between the glass and the float plate glass can be measured by the above-mentioned method, and more specifically, can be measured by the method described in Examples of the present application.

[0204] The shear strength of the molded article of the present invention with respect to the float glass measured under the above-mentioned specific conditions can be appropriately adjusted by selecting and adjusting the components constituting the molded article, in particular the (D) lubricant, the materials of other components, the blending amounts, etc. Particularly effective adjustment means include: using (D1) monofatty acid amide and (D2) bisfatty acid amide as (D) lubricant and adjusting the mass ratio of the two; increasing the amount of (C) propylene polymer, etc.

[0205] The molded article of the present invention is preferably heated to 220°C and sheared at a rate of 12 seconds -1 The melt viscosity measured under the conditions is less than 2500 Pa•s.

[0206] Since the melt viscosity is 2500 Pa•s or less, the molded body of this embodiment has high fluidity and excellent moldability when molded by injection molding or the like in its molding process, and the molded body has good appearance such as surface smoothness and excellent bonding properties with other components.

[0207] The melt viscosity can be measured by melting a molded article at a predetermined temperature and measuring the melt viscosity at a predetermined shear rate according to a method known in the art.

[0208] The melt viscosity can be appropriately increased or decreased by adjusting the content ratio or melt flow rate of the (C) propylene-based polymer used in the molded article, the ratio or particle size of the island phase of the sea-island structure generally composed of the (A) ethylene-based copolymer and / or the (B) copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, the gel fraction, and the like.

[0209] There is no particular limitation on the method for producing the molded article of the present invention. The molded article can be produced by mixing a mixture of (A) an ethylene copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound as a raw material, (C) a propylene polymer, and (D) a lubricant, and various additives as required by conventional methods using a conventional extruder, Banbury mixer, roll, Brabender mixer, Brabender kneader, etc. It is preferably produced by melt mixing using an extruder, especially a twin-screw extruder. In addition, all the components to be mixed can be melt mixed at one time, a part of the components can be mixed and then the remaining components can be added and melt mixed, or melt mixing can be performed once or twice or more. The temperature during melt mixing is preferably 150°C to 300°C, and more preferably 180°C to 250°C. The time for melt kneading is preferably 20 seconds to 30 minutes, more preferably 30 seconds to 20 minutes. The components to be kneaded may be added in any order or simultaneously.

[0210] When producing the molded article of the present invention, crosslinking may be performed or non-crosslinking may be performed. From the viewpoint of controlling the sea-island structure and melt viscosity, crosslinking is preferably performed.

[0211] In a preferred production method in the case of crosslinking, the following step is preferably performed: a mixture containing at least one component selected from (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer and (D) a lubricant is melt-kneaded in the presence of (F) a crosslinking agent.

[0212] When (A) an ethylene-based copolymer is used, it is preferred that the Mooney viscosity (ML) of the (A) ethylene-based copolymer be 1+4 The (C) propylene-based polymer has a melt flow rate measured at a temperature of 230° C. and a load of 21.18 N of 0.3 (g / 10 min) to 200 (g / 10 min).

[0213] When (A) the ethylene copolymer is filled with (E) mineral oil, it is preferred to perform the following step: melt-kneading the oil-filled polymer containing (E) mineral oil and (A) the ethylene copolymer, (C) the propylene polymer and (D) the lubricant in the presence of (F) a crosslinking agent. The Mooney viscosity (ML) of the oil-filled polymer is preferably 1+4The (C) propylene-based polymer has a melt flow rate measured at a temperature of 230° C. and a load of 21.18 N of 0.3 (g / 10 min) to 200 (g / 10 min).

[0214] The molded article of the present invention is preferably used for various applications for which thermoplastic elastomers have been conventionally suitably used, and is particularly preferably used to constitute a part or all of various members or products produced by injection molding or extrusion molding.

[0215] Furthermore, when the molded article of the present invention is used, an extrusion molded article or an injection molded article having excellent surface smoothness can be obtained, and thus it can be particularly preferably used in applications requiring a smooth molded article appearance.

[0216] The surface smoothness can be evaluated by measuring the ten-point average roughness of the surface of the molded product, for example.

[0217] Furthermore, the molded article of the present invention has excellent bonding properties with other members, particularly members composed of a thermoplastic elastomer composition using a propylene-based polymer as a sea phase, and can therefore be particularly preferably used when producing a composite molded article with such a member.

[0218] More specifically, preferred uses of the molded article of the present invention include, but are not limited to: parts represented by various automotive interior and exterior parts such as glass run channels, weather strips, door surrounds, instrument panels, glove boxes, decorative parts, housings, pillars, bumpers, fenders, and rear doors; various parts for home appliances, various housing equipment machine parts, various industrial parts, and various building material parts.

[0219] The injection molded article as a preferred embodiment of the present invention can be produced by using a thermoplastic elastomer composition having substantially the same proportion as the molded article of the present invention, for example, by using a conventional injection molding method, or by using various molding methods such as gas injection molding, injection compression molding, and short shot foaming molding as required. There is no particular limitation on the molding conditions in the above injection molding, and it can usually be carried out under the conditions of a molding temperature of 100°C to 300°C, preferably 180°C to 280°C, an injection pressure of 5MPa to 100MPa, preferably 10MPa to 80MPa, and a mold temperature of 20°C to 80°C, preferably 20°C to 60°C.

[0220] The injection molded article as a preferred embodiment of the present invention can be bonded to other members by utilizing its excellent bonding properties to form a composite molded article. As other members in this case, an extrusion molded article comprising a thermoplastic elastomer composition or a vulcanized rubber composition can be cited. It is preferred to use a molded article comprising a thermoplastic elastomer composition of the same type and ratio as the molded article of the present invention, particularly a molded article comprising a thermoplastic elastomer composition having a sea phase of a sea-island structure composed of a propylene-based polymer, because in this case, more excellent bonding properties can be achieved.

[0221] The bonding strength with other members in this embodiment is preferably 3.0 MPa or more, more preferably 3.3 MPa or more, and particularly preferably 3.5 MPa or more.

[0222] The higher the bonding strength with other members, the better. There is no particular upper limit, but in the case of producing a composite molded product at a practical cost, it is usually 6.0 MPa or less in many cases.

[0223] When manufacturing the composite molded body of the present embodiment, it is preferred that other members such as an extruded molded body are arranged in a mold, and then a thermoplastic elastomer composition having the same composition as the molded body of the present invention is injection molded in the mold, thereby joining the other members to the molded body of the present invention to manufacture the composite molded body. For example, the main body (straight part) of the glass run channel, which is the extruded molded body, is arranged in a mold for injection molding, and then the molded body of the present invention is formed by injection molding, thereby forming a corner part joined to the main body part, thereby manufacturing a glass run channel excellent in appearance, bonding strength between the main body part and the corner part, etc.

[0224] The molded article of the present invention can effectively suppress the peeling sound from the glass, and therefore, when used in a glass run, can effectively suppress the abnormal sound generated when the glass is raised and lowered.

[0225] Example

[0226] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples.

[0227] The physical properties and characteristics in Examples and Comparative Examples were evaluated by the following methods.

[0228] 1. Method for manufacturing injection molded article

[0229] The thermoplastic elastomer compositions produced in the Examples and Comparative Examples were injection molded using an IS100EN-3A injection molding machine manufactured by Toshiba Machine Co., Ltd. at a molding temperature of 220° C. and a mold temperature of 50° C. to obtain injection molded bodies having a length of 150 mm, a width of 90 mm, and a thickness of 2.0 mm.

[0230] 2. Rigidity (flexural modulus)

[0231] The flexural modulus of the injection molded article produced in 1. above was measured in accordance with JIS K7171 under the conditions of a standard atmosphere of 23° C. / 50% RH and a test speed of 1 mm / min.

[0232] 3. Evaluation of bonding properties with thermoplastic elastomer molded products

[0233] The thermoplastic elastomer molded product (Y) obtained in [Reference Example 1] described later was used as a material to be joined. First, the thermoplastic elastomer molded product (Y) was set in a mold for injection molding.

[0234] Then, the thermoplastic elastomer composition produced in each Example / Comparative Example was injection molded using an IS100EN-3A injection molding machine manufactured by Toshiba Machine Co., Ltd. under the conditions of a molding temperature of 250° C. and a mold temperature of 50° C., thereby obtaining a composite molded body (Z1) in which the above-mentioned thermoplastic elastomer molded body (Y) and the injection molded body containing the thermoplastic elastomer composition obtained in each Example / Comparative Example were partially melt-bonded.

[0235] The molded product (Z1) was punched out using a dumbbell of JIS K6251 No. 3 shape so as to include the molten joint surface perpendicularly to the length direction of the test piece, thereby preparing a test piece. The test piece was subjected to a pulling test at a pulling speed of 200 mm / min and a standard atmosphere of 23°C / 50%RH to evaluate the bonding strength.

[0236] [Reference Example 1]

[0237] (Preparation of Thermoplastic Elastomer Molded Article (Y))

[0238] Thermoplastic elastomer "SANTOPRENE 121-73W175" manufactured by ExxonMobil was injection molded using an IS100EN-3A injection molding machine manufactured by Toshiba Machine Co., Ltd. under the conditions of molding temperature 220°C, mold temperature 50°C, injection time 10 seconds, and cooling time 30 seconds to obtain an injection molded body (length 150 mm, width 90 mm, thickness 2.0 mm). Next, the injection molded body was cut with a cutter to have a length of 30 mm, a width of 90 mm, and a thickness of 2.0 mm, and the resulting body was used as a thermoplastic elastomer molded body (Y).

[0239] 4. Shear strength with glass

[0240] Two test pieces of 50 mm in length and 6 mm in width were punched out from a 2 mm thick pressed sheet obtained by press molding the thermoplastic elastomer composition produced in the examples and comparative examples described below under the following molding conditions. The test pieces were arranged in parallel on a SUS plate of 100 mm in length, 100 mm in width, and 1.5 mm in thickness in such a way that the opposing 50 mm × 2 mm surfaces were 60 mm apart from each other, and were adhered to the 50 mm × 6 mm surface using a double-sided tape. On the other 50 mm × 6 mm surface of the test piece, a float glass of 110 mm in length, 110 mm in width, and 3.0 mm in thickness according to JIS R3202 was placed, and was placed in an oven at 80°C for 50 hours, and then air-cooled for 12 hours at 23°C / 50%RH in a standard atmosphere. The float glass was subjected to a tensile test at 200 mm / min and 23°C / 50%RH along the length direction of the test piece, and the shear strength ([ Figure 1 ]).

[0241] • Molding conditions: The thermoplastic elastomer composition was sandwiched between polyester films, heated and pressed at a temperature of 200°C and a maximum pressure of 10 MPa for 5 minutes, and then cooled and pressed at a temperature of 23°C and a maximum pressure of 10 MPa for 5 minutes to produce a pressed sheet.

[0242] 5. Sound of peeling off from glass

[0243] In the test of 4. above, the tester measured the presence or absence of sound when the test piece and the float glass were peeled off from a position about 30 cm away from the test piece twice and evaluated the average value based on the following 5 levels. The average difference between the two measured values ​​was 0.4, indicating that the measured value was reliable.

[0244] 1: You can hear a very loud sound when peeling

[0245] 2: You can hear a loud sound when peeling

[0246] 3: The sound of peeling can be heard but it is small

[0247] 4: The sound of peeling can be heard very small

[0248] 5: No sound can be heard when peeling

[0249] The details of the materials used in Examples and Comparative Examples are as follows.

[0250] <Component (A)> Ethylene copolymer

[0251] (A1-i)+(E)

[0252] Oil-extended ethylene-propylene-5-ethylidene-2-norbornene copolymer (a mixture of 100 parts by mass of component (A1-i) and 100 parts by mass of component (E))

[0253] Mooney viscosity of (A1-i) + (E) (ML 1+4 125℃)=47

[0254] The Mooney viscosity (ML) of (A1-i) calculated by the above formula (1) 1+4 125℃)=215

[0255] Composition of (A1-i)

[0256] Ratio of structural units derived from ethylene = 70.0 mass %

[0257] Ratio of structural units derived from propylene = 21.5 mass %

[0258] Ratio of structural units derived from 5-ethylidene-2-norbornene = 8.5% by mass

[0259] <Component (B)> A component having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound The copolymer of the structural unit

[0260] (Bi): manufactured by TSRC Corporation, trade name “TAIPOL (registered trademark) 6151”, ratio of monomer units derived from styrene = 32.5% by mass, weight average molecular weight in terms of polystyrene = 240,000

[0261] <Component (C)> Propylene polymer

[0262] (C1-i): Propylene homopolymer, manufactured by Sumitomo Chemical Co., Ltd., trade name "Sumitomo NOBLEN D101", MFR (230°C, 21.18N) = 0.5 g / 10 min

[0263] (C1-ii): Propylene homopolymer, manufactured by Sumitomo Chemical Co., Ltd., trade name "Sumitomo NOBLEN R101", MFR (230°C, 21.18N) = 20 g / 10 min

[0264] <Component (D)> Lubricant

[0265] (D1-i): Erucamide, manufactured by Nippon Seika Co., Ltd., trade name "NEUTRON S", molecular weight = 338

[0266] (D2-i): Ethylene bisstearamide, manufactured by NOF Corporation, trade name "ALFLOW H-50P", molecular weight = 593

[0267] <Component (F)> Crosslinking agent

[0268] (Fi) + (Ei): manufactured by Akzo Chemicals Co., Ltd., trade name "APO-10 DL" (a mixture of 10% by mass of the component (Fi) and 90% by mass of the component (Ei) (wherein the total amount of (Fi) and (Ei) is 100% by mass))

[0269] (Fi): 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane

[0270] <Ingredient (E)> Mineral oil

[0271] (Ei): Paraffin-based mineral oil, manufactured by Idemitsu Kosan Co., Ltd., trade name "PW-100", pour point = -12.5°C

[0272] Crosslinking aid: Sumitomo Chemical Co., Ltd., trade name "Sumifine BM" (N,N'-m-phenylene bismaleimide)

[0273] Antioxidant: BASF Japan Ltd., trade name "IRGANOX (registered trademark) 1010"

[0274] Black pigment masterbatch: manufactured by Sumika Color Co., Ltd., trade name "PEM8080G"

[0275] <Example 1>

[0276] 75.0 parts by mass of an oil-extended ethylene random copolymer ((A1-i) + (E)), 20.0 parts by mass of a propylene homopolymer (C1-i), 0.125 parts by mass of a fatty acid amide (D1-i), 0.2 parts by mass of a fatty acid amide (D2-i), 3 parts by mass of a crosslinking agent ((Ei) + (Fi)), 0.1 parts by mass of a crosslinking aid, 0.2 parts by mass of an antioxidant and 1.2 parts by mass of a pigment were melt-kneaded at a cylinder temperature of 200°C±20°C in an upstream step of a twin-screw extruder (TEX34αIII) manufactured by The Nippon Steel Works, Ltd., and 5 parts by mass of a propylene homopolymer (C1-i) were melt-kneaded at a cylinder temperature of 200°C±20°C in a downstream step of the twin-screw extruder, thereby obtaining a thermoplastic elastomer composition. The obtained thermoplastic elastomer composition was injection molded by the method (1) or (3) above, and press molded by the method (4) above to obtain a molded body. The results of measuring the physical properties of the molded body and the evaluation results of the bonding properties with the thermoplastic elastomer molded body are shown in Table 1.

[0277] <Examples 2 to 5 and Comparative Examples 1 and 2>

[0278] Except for changing the compounding ratio of the raw materials as shown in Table 1, a thermoplastic elastomer molded article was produced and evaluated in the same manner as in Example 1.

[0279] Table 1 shows the results.

[0280] [Table 1]

[0281]

[0282] Industrial Applicability

[0283] The thermoplastic elastomer molded article of the present invention can effectively suppress the peeling sound from the glass and has excellent bonding properties with other members. Therefore, it is suitable for use in various automotive interior and exterior parts such as glass run channels, weather strips, door rings, instrument panels, glove boxes, decorative parts, housings, pillars, bumpers, fenders, and tailgates, various parts for home appliances, various housing equipment parts, various industrial parts, and various building material parts. It has high practicality in various fields of industries such as the transportation machinery industry, the electrical and electronic industry, and the building construction industry.

Claims

1. A molded article comprising: at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant, wherein: The flexural modulus of the molded article at room temperature measured in accordance with JIS K7171 is 20 MPa or more and 300 MPa or less, Two test pieces of length 50 mm×width 6 mm×thickness 2 mm cut out from the molded body were arranged on a flat plate with the 50 mm×2 mm surfaces facing each other at an interval of 60 mm, and the two test pieces were fixed on the flat plate with the 50 mm×6 mm surfaces, so that the other 50 mm×6 mm surfaces of the two test pieces were directly in contact with the 110 mm×110 mm surface of a float plate glass of length 110 mm×width 110 mm×thickness 3 mm according to JIS R 3202, and left to stand at 80° C. for 50 hours, and then the interlayer between the two test pieces and the float plate glass was pulled at 200 mm / min in the shear direction and the length direction of the test pieces, and the shear strength at this time was 40 N / cm 2 the following.

2. The molded article according to claim 1, wherein The molded article contains (A) an ethylene-based copolymer.

3. The molded article according to claim 2, wherein The shaped body further contains (E) mineral oil.

4. The molded article according to claim 3, wherein (A) Ethylene copolymer filled with (E) mineral oil.

5. The molded article according to claim 1, wherein The molded article contains (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound.

6. The molded article according to claim 5, wherein The shaped body further contains (E) mineral oil.

7. The molded article according to any one of claims 1 to 6, wherein The (D) lubricant contains at least (D1) monofatty acid amide and (D2) bisfatty acid amide, and the mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide is in the range of 0.2-5.

8. The molded article according to claim 7, wherein The mass ratio of (D1) monofatty acid amide / (D2) bisfatty acid amide is in the range of 0.2-1.

9. The molded article according to claim 7 or 8, wherein (D1) The monofatty acid amide is erucamide.

10. The molded article according to any one of claims 7 to 9, wherein (D2) The bisfatty acid amide is ethylene bisstearamide.

11. (A) A method for producing the molded article according to any one of claims 1 to 10, wherein: The method comprises the step of melt-kneading a mixture in the presence of (F) a cross-linking agent, wherein the mixture contains: at least one component selected from the group consisting of (A) an ethylene-based copolymer and (B) a copolymer having a structural unit derived from an aromatic vinyl compound and a structural unit derived from a conjugated diene compound, (C) a propylene-based polymer, and (D) a lubricant.

12. The molded article according to any one of claims 1 to 10, wherein The molded body is an injection molded body.

13. A composite molded body, wherein: The composite molded body is obtained by joining the injection molded body according to claim 12 with an extrusion molded body, wherein the extrusion molded body comprises a thermoplastic elastomer composition or a vulcanized rubber composition.

14. The composite molded body according to claim 13, wherein The composite molded body is a glass run.

Citation Information

Patent Citations

  • Hydrogenation of polymer

    JP1984133203A

  • Hydrogenation of living polymer

    JP1985079005A

  • Production of alpha-olefin polymer

    JP1986218606A

  • Production of alpha-olefin polymer

    JP1986287904A

  • Ethylene-propylene block copolymer

    JP1993194685A